2011
DOI: 10.1111/j.1399-3046.2011.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric health‐related quality of life after intestinal transplantation

Abstract: As outcomes after ITx improve, greater emphasis is needed on HRQOL. The primary aims of this study were to (i) assess the feasibility of measuring HRQOL in pediatric ITx recipients, (ii) measure HRQOL using validated instruments, and (iii) compare HRQOL in ITx recipients to healthy normal (NL) children. The CHQ and Pediatric Quality of Life (PedsQL4.0) instruments were administered to both patients and parents at outpatient visits. All 24 eligible patients were enrolled. The median age at study enrollment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 19 publications
7
29
0
1
Order By: Relevance
“…Consistent with prior studies of acute postsurgical pain experienced while in the hospital 13 , the majority of children in our sample also reported moderate-severe pain that persisted at two weeks after surgery. As expected, children also reported health-related quality of life impairments 2 weeks after major surgery, which is consistent with studies of HRQOL at long-term follow-up in children after major surgeries 9,22,30 . Physical health was markedly impaired with average levels 6.2 standard deviations below established mean scores for children without a chronic health condition 2 .…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with prior studies of acute postsurgical pain experienced while in the hospital 13 , the majority of children in our sample also reported moderate-severe pain that persisted at two weeks after surgery. As expected, children also reported health-related quality of life impairments 2 weeks after major surgery, which is consistent with studies of HRQOL at long-term follow-up in children after major surgeries 9,22,30 . Physical health was markedly impaired with average levels 6.2 standard deviations below established mean scores for children without a chronic health condition 2 .…”
Section: Discussionsupporting
confidence: 88%
“…Our analysis showed that inclusion of the colon did not adversely affect survival and recipients with a colon segment had a 5% higher rate of independence from supplemental PN. These findings are consistent with individual program reports (36,37) and experimental data showing that retention of the ileocecal valve and the right colon enhance gut function through better fluid absorption and uptake of free fatty acids (38)(39)(40)(41)(42)(43). Since IT recipients frequently experience motility and absorption issues posttransplant (33), it is worthwhile to consider if including a colon segment with an intestinal transplant should become the standard of care.…”
Section: Discussionsupporting
confidence: 80%
“…By 6 months after transplantation, the ITR data show that most recipients resume an oral diet and return to normal activities. Individual center studies recently reported have also documented that (1) adult IT recipients return to work and enjoy a good quality of life (33) and (2) pediatric recipients resume oral nutrition and enjoy catchup growth and an improved quality of life (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Quality-of-life (QOL) has been demonstrated to be better after intestine transplantation compared to patients remaining on PN (56)(57)(58). In two studies of QOL after intestine transplantation, the presence of G-tubes or ostomies and repeat hospitalization were factors associated with decreased scores (56,58).…”
Section: Quality Of Lifementioning
confidence: 99%
“…In two studies of QOL after intestine transplantation, the presence of G-tubes or ostomies and repeat hospitalization were factors associated with decreased scores (56,58). The Pittsburgh group (57) compared QOL before and after intestine transplantation in 76 surviving adult recipients with mixed results.…”
Section: Quality Of Lifementioning
confidence: 99%